Διερεύνηση δεικτών αποτίμησης της ενεργειακής αποδοτικότητας στην Ελλάδα - Σπύρου, Αλεξάνδρα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Ηλεκτρικών Βιομηχανικών Διατάξεων και Συστημάτων Αποφάσεων. Εργαστήριο Συστημάτων Αποφάσεων και Διοίκησης, 2016)
Increasing energy efficiency is one of the most stable EU headline targets in recent years. The main European target set for 2020 refers to primary energy savings of 20%. In the tracking of the submitted National Energy Efficiency Action Plans ( NEEAPs ) of EU Member States the need to update the legislation was explicit, and for this purpose EU adopted the Directive 2012/27 / EC, replacing Directive 2006/32 / EC on energy end-use efficiency and energy services. Each Member State has the freedom to set indicative national energy efficiency target for 2020, so as to achieve the European target. Greece has established a national energy efficiency target of achieving final energy consumption of 18.4 MToe by 2020. The target was chosen on the basis of final energy consumption, mainly because final energy consumption specifies energy demand. Therefore, a national strategy was decided concluding the adoption of a set of measures and policies in order to accomplish final energy consumption not to exceed 18.4Mtoe, which will lead to improved energy efficiency. In this context , the aim of this diploma dissertation is the investigation and collection of green economy indicators and the statistical correlation with the final energy consumption, which reflects the energy demand of the country. This methodology will allow to identify the appropriate set of indicators, which will pinpoint the progress towards energy efficiency in Greece.